PREOPERATIVE, INTRAOPERATIVE AND POSTOPERATIVE PREDICTORS ASSOCIATED WITH COMPLICATIONS AND SURVIVAL OF PATIENTS AFTER COLORECTAL RESECTION - Marković, Teodora; Grujičić, Sandra (HEALTH CARE, 2025)
Colorectal cancer is the third most commonly diagnosed form of all cancers, and the second deadliest cancer worldwide. The International Agency for Research on Cancer (IARC) estimates that the global burden of colorectal cancer on society will increase by 60%, representing more than 2.2 million new cases and 1.1 million deaths by the year 2030. The aim of this review paper is to show which predictors, at hat point in the course of the disease, and in what way they influence the occurrence of postoperative complications and the survival of patients with colorectal cancer. Elevated levels of inflammatory markers, poor nutritional status, a higher category of the ASA (American Society of Anesthesiologists) physical status classification, and poor lifestyle habits represent significant independent predictors of poor survival and increase the risk of developing postoperative complications after resection. Intraoperatively, longer duration of the operation and significant blood loss during surgery contribute to poor outcomes. Postoperative complications (anastomotic leakage, postoperative bleeding, intra-abdominal abscess, stoma complications, general complications) independently increase the risk of mortality after surgery.